The impact of parental overprotection on the emotions and behaviors of pediatric hematologic cancer patients: a multicenter cross-sectional study - Yu, Yahui; Zheng, Xiaofeng; Xu, Wenjing; Huang, Yuru; Wang, Xulu; Hong, Wanting; Wang, Runping; Ye, Xiaojing; Zhang, Chunmei (Frontiers in Psychology, 2024)
Background: Parental overprotection may have an impact on children's emotional and behavioral problems (EBPs). Pediatric leukemia patients have compromised immune systems, and parents often excessively worry, leading to excessive interference in their lives. Therefore, avoiding overprotection is crucial for the overall physical and mental health of pediatric leukemia patients. Aims: The aim of this study is to examine the current status of EBPs in pediatric leukemia patients and analyze their associated risk factors. Design: This work was a multicenter cross-sectional observational and correlational study. We collected data anonymously through parental questionnaires from three pediatric hematologic oncology hospitals in China. The Strengths and Difficulties Questionnaire, the Parental Overprotection Measure (POM) scale, and a general information survey designed by the research team were employed to assess children's EBPs, the degree of parental overprotection, as well as basic demographic and disease-related information. Chi-square tests and generalized linear mixed-effects regression analysis were used to analyze the factors influencing EBPs among pediatric leukemia patients. Setting and participants: Using a convenience sampling method, a total of 202 participants' parents were selected. All participants were invited to complete the questionnaire through one-on-one guidance. Results: Emotional symptoms accounted for the highest proportion of abnormal EBPs in children (27.72%), followed by peer problems (26.24%), prosocial behavior (25.74%), behavioral problems (14.36%), and total difficulties (13.86%). A minority of children had abnormal hyperactivity scores (4.95%). The results of a generalized linear mixed regression analysis This is a provisional file, not the final typeset article showed that age, duration of illness, and parental overprotection were significant factors influencing abnormal EBPs in children (p < 0.05). A POM score threshold of 37 exhibited good sensitivity (74%) and specificity (90%) in predicting abnormal EBPs in children. Conclusion: Children with blood cancer under excessive parental protection are more prone to experiencing EBPs. Healthcare professionals should guide parents to reduce this excessive protection, as it can help mitigate the occurrence of EBPs in children.